Pemeriksaan Glukosa pada Masyarakat di Desa Kel. Boneoge, Kec. Banawa Kab. Donggala - Juhri Juhri; Hermin Lastri Gintoe; Slamet Ifandi (Universitas 45 Surabaya, 2025)
Blood glucose testing is a crucial step in the early detection of diabetes mellitus (DM), especially in remote areas such as Boneoge Village, Banawa District, Donggala Regency. This study aims to raise community awareness about the importance of blood glucose testing and provide free testing access. The methods used include direct blood glucose testing and health education for participants. A total of 28 individuals participated, with results indicating that 5 participants had elevated blood glucose levels (>200 mg/dL), while 23 had normal levels (<200 mg/dL). These findings highlight the need for increased community understanding of diabetes risks and the importance of routine health screenings. .